Income distribution, the Great Depression, and the relative income hypothesis - Christian A. Belabed (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
This paper discusses the rise of top-end inequality and its effects on household consumption, saving, and debt in the United States during the 1920s by applying a non-standard theory of consumption, the relative income hypothesis, to the period of interest. Analysing the relevant data descriptively, the paper argues that income inequality is linked to the increase of household consumption and the simultaneous decline of household savings as well as rapidly increasing household debt. Thus, the rise of top-end inequality in connection with a broader institutional change, such as the deregulation of financial markets, has contributed to a build-up of financial and macroeconomic instability in the period leading to the Great Depression.
Keywords: D31; D33; E21; E25; N12; N22; N32; N62; 330; income distribution; relative income hypothesis; household debt; financial innovation; Great Depression